(untitled) (International Journal of Engineering and Computer Science, 2016)
This paper presents an algorithm for the Mobile License Plate Reader System using various approaches. Mobile license plate reader (MLPR) technique consists of two modules, a license plate locating module and a license number identification module. In this paper, an experimental extraction of image is performed with PCA (Principle Component Analysis), Segmentation is performed with OCR (Optical Character Recognition) and Recognition is performed with SVM (Support Vector Machine) which are based on original binary images of the characters. The training via support vector machine has yielded the accurate outputs for the recognition of various input images taken in the algorithm. The purpose of this paper is to develop a real time application which recognizes license plates from cars at a gate, for example at the entrance of a parking area or a border crossing. Recognition of about 98% vehicles shows that the system is quite efficient